Trend Promosi Perguruan Tinggi yang Ampuh dalam Menarik Minat Mahasiswa Baru (Studi Kasus Perguruan Tinggi di Kota Palembang) - Rabial Kanada (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2019)
Along with competition between competitive educational institutions, promotion is important to introduce strategies and programs from educational institutions to the wider community so that they are aware of the efforts that will be made by educational institutions for the advancement of their children. It is undeniable that promotion activities have more or less influenced the stabilization of people's choices for educational institutions. The approach used is a mix method by combining qualitative and quantitative methods. Data collection techniques using questionnaires and interviews. Questionnaires are used to get quantitative data related to the type of promotion and media used by the campus, while interviews get qualitative data to strengthen quantitative data or add data that is not revealed to quantitative data. The data source is the campus in the city of Palembang, students, alumni, and the community in the province of South Sumatra. The results showed 100% of universities in Palembang conducted direct promotions and advertisements, while the results of the questionnaire to related new students who influenced them in choosing tertiary institutions showed that under 10% of campus direct promotions, 20% were advertisements, and 70% others. Another dimension here is the influence of students, alumni, and parents / guardians.